(untitled) (MMIT Proceedings, 2025)
This article focuses on the classification of routing algorithms, the application of flexible and non-flexible routing algorithms, and analyzes routing protocols that ensure the security of the five main networks. Network protocols are considered, which have the characteristics of choosing a suitable, accurate, and secure route for simple and small networks, working at the entire Internet level, providing fast operation and strong results, and ensuring stable and efficient network operation.